An improved windowed Fourier transform filter algorithm. (November 2015) - Zhao, Ran; Li, Xinglong; Sun, Ping
Abstract: In order to reduce the speckle noise in fringe patterns obtained by Electric Speckle Pattern Interferometry (ESPI), an improved windowed Fourier transform filter algorithm was proposed. The amplitude maximum of the fringe frequency scanned across a given window is set as the filtering criterion, which the optimum frequency image is obtained and the threshold window is not set in the window Fourier filter algorithm. The proposed algorithm is used to filter the fringe patterns obtained by ESPI. Experiment results show that the proposed algorithm has a better performance in reducing the speckle noise and has a high precision in phase calculation. The proposed algorithm can be used to filter other image as a low-pass filter. Highlights: The threshold is not required to be set in advance. The filtering criterion is the maximum amplitude at the local area in spectrum. The effect of the new algorithm on suppressing speckle noises is perfect. Better performance in reducing computing time and operation simply. The new algorithm can be used to process image as a low-pass filter.